Knot bad amigurumi : learn crochet stitches and techniques to create cute creatures with 25 easy patterns - Green-Hite, Vincent (Quarry Books, 2022)
"Knot Bad Amigurumi features easy and fun techniques for creating unique and adorable crochet characters-including a turtle, bee, rocket ship, and boba tea, along with ideas for personalizing creations"--